Urban agriculture in Maputo - Christie, Frances, Michele (My University, 1996)
This report covers the development of agricultural production in Maputo city, After reviewing the llterature on urban agriculture, it examines the polltlcal and legal framework for the practice of agriculture production in the Mozambican capital, The development of institutions designed to support small-scale producers is then investigated. ( Abbreviation abstract )
A research report submitted to the Faculty of Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Management (in the field of Public and Development Management ).
Keywords: Urban agriculture -- Mozambique -- Maputo.; Land use, Urban -- Mozambique -- Maputo.; Vegetable gardening -- Mozambique -- Maputo.; Agriculture -- Mozambique -- Maputo; Small business -- Mozambique -- Maputo